Erbium complexes as pioneers for implementing linear light-upconversion in molecules. Issue 5 (19th February 2020) - Golesorkhi, Bahman; Nozary, Homayoun; Fürstenberg, Alexandre; Piguet, Claude
Abstract : Trivalent erbium, Er 3+, with its 4f 11 electronic configuration, was the first lanthanide cation for which linear upconversion could be induced in a molecular complex. The reasons for this success and its perspectives are discussed in this review. Abstract : Since the non-linear optical (NLO) response of matter to incident excitation light does not require long-lived intermediate excited states working as relays, the conversion of low-energy photons into high energy light beams using second-harmonic generation (second-order NLO process) or two-photon absorption (third-order NLO process) can be implemented either in low-phonon macroscopic solids or in molecules containing high-energy vibrations. However, harnessing the very weak non-linear absorption coefficients requires (very) intense excitation sources, typically lasers, for getting reasonable emitted intensities. In contrast, the piling of successive near-infrared photons to get visible emission using linear optics, i.e. upconversion, is much more efficient, but it depends on the existence of intermediate excited states possessing long residence lifetimes. Therefore, upconversion usually occurs in low-phonon ionic solids or nanoparticles doped with pertinent activators. The recent recognition that trivalent erbium coordination complexes possessing high-frequency oscillators may act as dual visible/near-infrared activators, which implies the existence of at least one long-lived intermediate excited state in these complexes, paved the way for the implementation of the first upconversion processes within isolated molecules. Beyond a justification for using trivalent lanthanides, and especially erbium, for the manipulation of the energy of photons in molecules using linear optics, this tutorial review summarizes the current level of developments in the field of molecular-based upconversion and discusses some forthcoming challenges.